Social interaction and urban sprawl - Jan Keith Brueckner; Ann G. Largey (Center for Economic Studies and ifo Institute (CESifo), 2006)
Various authors, most notably Putnam (2000), have argued that low-density living reduces social capital and thus social interaction, and this argument has been used to buttress criticisms of urban sprawl. If low densities in fact reduce social interaction, then an externality arises, validating Putnam's critique. In choosing their own lot sizes, consumers would fail to consider the loss of interaction benefits for their neighbors when lot size is increased. Lot sizes would then be inefficiently large, and cities excessively spread out. The paper tests the premise of this argument (the existence of a positive link between interaction and density) using data from the Social Capital Benchmark Survey. In the empirical work, social interaction measures for individual survey respondents are regressed on census-tract density and a host of household characteristics, using an instrumental-variable approach to control for the potential endogeneity of density.
Keywords: R1; J11; 330; Urbanisierung; Soziale Beziehungen; USA